The effect of the focus strategy on the achievement of literature among fifth grade female students (Journal of the College of Basic Education, 2024)
The current research aims to identify the effect of the focus strategy on the achievement of literature among fifth-grade female students in middle school. The research sample was: (60) female students from the fifth grade of middle school in Al-Nasr Preparatory School for Girls affiliated with the Baghdad Al-Karkh Third Education Directorate, for the academic year (2023-2024) were chosen randomly to implement the experiment, where Section (D) represented the experimental group with (30) students, and Section (B) represented The control group consisted of (30) female students. The researcher prepared (an achievement test) as a research tool. It consisted of (thirty-six) test items consisting of objective items (multiple choice with four alternatives), and its validity and reliability were verified. After implementing the experiment, the researcher applied the achievement test and using the statistical package (SPSS-28), the results of the current research showed (the superiority of the female students of the experimental group who studied literature according to the focus strategy over the female students of the control group who studied the same subject using... Ordinary (traditional) method in the post-achievement test.